Genomic Analysis and Antimicrobial Resistance of Campylobacter jejuni and Campylobacter coli in Peru - Quino, Willi; Caro-Castro, Junior; Hurtado, Verónica; Flores-León, Diana; Gonzalez-Escalona, Narjol; Gavilan, Ronnie G. (Frontiers in Microbiology, 2022)
Campylobacter is the leading cause of human bacterial gastroenteritis worldwide and has a major impact on global public health. Whole Genome Sequencing (WGS) is a powerful tool applied in the study of foodborne pathogens. The objective of the present study was to apply WGS to determine the genetic diversity, virulence factors and determinants of antimicrobial resistance of the populations of C. jejuni and C. coli in Peru. A total of 129 Campylobacter strains (108 C. jejuni and 21 C. coli) were sequenced using Illumina Miseq platform. In silico MLST analysis identified a high genetic diversity among those strains with 30 sequence types (STs), several of them within 11 clonal complexes (CC) for C. jejuni, while the strains of C. coli belonged to a single CC with 8 different STs. Phylogeny analysis showed that Peruvian C. jejuni strains were divided into 2 clades with 5 populations, while C. coli formed a single clade with 4 populations. Furthermore, in silico analyses showed the presence of several genes associated with adherence, colonization and invasion among both species: cadF (83.7%), jlpA (81.4%), racR (100%), dnaJ (83.7%), pebA (83.7%), pldA (82.1%), porA (84.5%), ceuE (82.9%), ciaB (78.3%), iamB (86.8%) and flaC (100%). The majority (82.9%) of the Campylobacter strains carried the cdtABC operon which code for cytolethal distending toxin. Half of them (50.4%) carried genes associated with the presence of T6SS, while the frequency of genes associated with T4SS were relatively low (11.6%). Genetic markers associated with resistance to quinolones, tetracycline (tetO, tetW/N/W), beta-lactamases (blaoxa-61), macrolides (A2075G in 23S rRNA) were found in 94.5%, 21.7%, 66.7%, 6.2%, 69.8% and 18.6% of strains, respectively. The cmeABC multidrug efflux operon was present in 78.3% of strains. This study highlights the importance of using WGS in the surveillance of emerging pathogens associated with foodborne diseases, providing genomic information on genetic diversity, virulence mechanisms and determinants of antimicrobial resistance. The description of several Campylobacter genotypes having many virulence factors and resistance to quinolones and tetracyclines circulating in Peru provides important information which helps in the monitoring, control and prevention strategies of this emerging pathogen in our country.